Application of CRM in Improving Sales Strategy at Second Branded Fashionable Stores Classy Range - Hasana, Dina Nur; Irianto, Irianto; Marpaung, Nasrun (Sistemasi: Jurnal Sistem Informasi, 2024)
Second branded fashionable classy range engaged in fashion thrifting clothing that sells a variety of thrifting clothing such as imported tops, pants, dresses, children's clothing and tunics. Thrifting clothes are second brand clothes that are still very feasible to resell or use, thrifting activities are very much in demand, especially teenagers because the prices are relatively cheap and affordable, making an attraction for teenagers. It is unfortunate that in the second year of the second branded fashionable classy range store experienced a decline in sales, so something is needed that can help increase sales and marketing. With the research conducted, the author produces a change that can help in the marketing and service process by creating a web-based information system with the help of application programs such as PHP and MySQL that combine CRM (Customer Relationship Management) strategies. CRM is a business strategy that focuses on good relationships with customers and companies, in designing the system also used 3 phases contained in CRM, namely customer acquisition, customer maintenance and customer development.